1982
DOI: 10.1007/bf00965528
|View full text |Cite
|
Sign up to set email alerts
|

Properties of phosphate activated glutaminase in astrocytes cultured from mouse brain

Abstract: Astrocytes in primary cultures contain a relatively high activity of phosphate activated glutaminase, although it is significantly lower than that of synaptosomal enriched preparations. The relatively high glutaminase activity in the astrocytes appears not to be caused by substrate induction, since a 10-fold variation in the glutamine concentration of the culture medium does not affect the activity. Of the reaction products, only glutamate inhibits astrocytic glutaminase whereas that of synaptosomal enriched p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 24 publications
3
51
0
Order By: Relevance
“…These results strongly indicate that the transmitter pool of glutamate is indeed affected by reduced numbers of synaptic vesicles in the synapsin DKO mice and that this finding most likely was overshadowed by the large metabolic pool of glutamate when studied in cerebrum extracts. Previous studies have shown that PAG, the enzyme catalyzing the conversion of glutamine to glutamate, is inhibited by even small increases in the intracellular levels of glutamate (Kvamme et al 1982;Hogstad et al 1988), similar to the inhibition of GAD by increased cytosolic GABA concentrations. The tendency towards a less pronounced increase in [4,[5][6][7][8][9][10][11][12][13] C]glutamate compared to [4,[5][6][7][8][9][10][11][12][13] C]glutamine in cerebrum extracts from synapsin DKO mice could indicate a decrease in the conversion of glutamine to glutamate, possibly by feedback inhibition of PAG.…”
Section: Discussionmentioning
confidence: 86%
“…These results strongly indicate that the transmitter pool of glutamate is indeed affected by reduced numbers of synaptic vesicles in the synapsin DKO mice and that this finding most likely was overshadowed by the large metabolic pool of glutamate when studied in cerebrum extracts. Previous studies have shown that PAG, the enzyme catalyzing the conversion of glutamine to glutamate, is inhibited by even small increases in the intracellular levels of glutamate (Kvamme et al 1982;Hogstad et al 1988), similar to the inhibition of GAD by increased cytosolic GABA concentrations. The tendency towards a less pronounced increase in [4,[5][6][7][8][9][10][11][12][13] C]glutamate compared to [4,[5][6][7][8][9][10][11][12][13] C]glutamine in cerebrum extracts from synapsin DKO mice could indicate a decrease in the conversion of glutamine to glutamate, possibly by feedback inhibition of PAG.…”
Section: Discussionmentioning
confidence: 86%
“…56 Preliminary studies have also shown a similar attenuation of the MPT, as well as reduction in ROS formation by histidine in cultured astrocytes treated with ammonia. 62 While PAG is clearly present in cultured astrocytes, [63][64][65] its localization in astrocytes in vivo is a matter of controversy. Some immunohistochemical studies have not shown PAG in glia 60,66 ; yet, other immunohistochemical, 67 enzyme histochemical studies, 68 as well as studies using bulk-isolated astrocytes, 69 have all shown a glial localization of PAG.…”
Section: The Trojan Horsementioning
confidence: 99%
“…Primary cultures of astrocytes displayed strong GA activity (63)(64)(65) and GA mRNA transcripts (66), but these in vitro results have been questioned claiming that GA could be induced by culture conditions (4). By contrast, contradictory results appear in the literature about the expression of GA in astrocytes: immunohistochemical studies have shown expression of GA protein and GA activity in rat brain astrocytes (32,67); however, no GA was found in astrocytes from rat cerebellum via post-embedding immunocytochemistry with colloidal gold (33).…”
Section: Function Of Ga In Glutamatergic Neurotransmissionmentioning
confidence: 99%